The Role Of Language In Intercultural Communication - Nasyrova Nargiza Akhmetovna (Academia One, 2025)
The article is devoted to the problem of studying the relationship of language and culture, which are important components of human life. The importance of the role of language in intercultural communication is shown. The basic functions of language (communication, cognition and influence) interacting in different acts of speech and in texts are considered. The features and factors contributing to the effectiveness of intercultural communication are studied. The influence of language on human behavior and culture is considered. The importance of intercultural communication in human life is shown, due to the ongoing processes of globalization of economic, political and cultural aspects of cooperation. The levels of implementation of intercultural communication are considered. The solution of important problems on the part of a person in the process of intercultural communication is shown.
Keywords: language; person; culture; intercultural communication